Water soluble dicarboxylic acids and related compounds in Antarctic aerosols - Kawamura, Kimitaka; Sempere, Richard; Imai, Yoshie; Fujii, Yoshiyuki; Hayashi, Masahiko (Journal of Geophysical Research: Atmospheres, 1996)
International audience Antarctic aerosols collected at Syowa Station were studied for water soluble organic compounds by employing a water extraction and dibutyl ester derivatization and using a capillary gas chromatography (GC) and GC/mass spectrometry (GC/MS). Total carbon and nitrogen were also determined. A homologous series of c•,o•-dicarboxylic acids (C2-Cll), 0./-oxoc&rboxylic &cids (C2-C9), and c•dicarbonyls (C2-C3) were detected, as well as pyruvic acid and aromatic (phthalic) diecid. Succinic (C4) or oxalic (C2) acid was found to be the dominant diecid species, followed by azelaic (C9), adipic (C6), or malonic (C3) acid. Concentration range of the total diacids was 5.9-88 ng m-3, with an average of 29 ng m-3. Highest concentrations were observed in the summer sample with a predominance of succinic acid (61.5 ng m-3), which comprised approximately 70% of the total diacids and accounted for 3.5% of total aerosol carbon (1020 ng m-3). The succinic acid (C4) is likely produced by photooxidation of 4-oxocarboxylic acids, which are present in the atmosphere as intermediates of the photooxidation of unsaturated fatty acids. These results indicate that the Antarctic organic aerosols originate from marine-derived lipids and are transformed largely by photochemical oxidations. c•-Oxocarboxylic acids (C2-C9, 0.36-3.0 ng m-3) also showed the highest concentration in the summer sample, again suggesting a secondary production in the atmosphere of the Antarctic and in the Southern Ocean.